Isolation and purification of recombinant outer surface protein C (rOspC) of Borrelia burgdorferi sensu lato - Křupka, Michal; Běláková, Jana; Šebestová, Martina; Tuháčková, Jana; Raška, Milan; Vrzal, Vladimír; Weigl, Evžen (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
The aim of this work was isolation and purification of the major immunodominant protein, Outer surface protein C (OspC) of three members of the species group Borrelia burgdorferi, the causative agent of Lyme disease. Our aim was to obtain this protein in a quantity and purity sufficient for immunization of experimental animals. For optimalization of protein purification's yield we used immobilized metal ion affinity chromatography (IMAC) under different conditions. The greatest efficiency was achieved by using of HiTrap Chelating Column under native conditions.
Keywords: vakcína proti lymeské nemoci; Antigens, Bacterial; Bacterial Outer Membrane Proteins; genetické vektory; Lyme Disease Vaccines; antigeny bakteriální; proteiny vnější bakteriální membrány; Escherichia coli; DNA vakcíny; Genetic Vectors; Vaccines, DNA